2013
DOI: 10.1364/oe.21.007821
|View full text |Cite
|
Sign up to set email alerts
|

Self-frequency-doubled BaTeMo_2O_9 Raman laser emitting at 589 nm

Abstract: In this paper, the spontaneous Raman spectra and second harmonic generation (SHG) properties at 589 nm of a novel Raman crystal BaTeMo(2)O(9) (BTM) were investigated. The BTM crystal was cut along the type-II SHG phase-matching direction for the first-order Raman shift at 1178 nm to realize the SRS and SHG simultaneously. Pumped by a nanosecond 1064 nm laser source, a self-frequency-doubled BTM Raman laser operating at 589 nm has been demonstrated for the first time. At the pump pulse energy of 48 mJ, the maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 16 publications
0
14
1
Order By: Relevance
“…In 2012, Yu et al confirmed that the BTM crystal has a wide transmission band (0.4-5 µm), large nonlinear coefficient (d 31 = 9.88 pm/V) and high optical damage threshold (544 MW/cm 2 ), flexible phase-matching, and high chemical, and mechanical stabilities [116]. Its strongest Raman shift is 915.2 cm −1 with line width of~4.4 cm −1 [6]. In 2013, the BTM crystal was employed as self-frequency-doubled Raman crystal to generate the yellow laser at 589 nm, as illustrated in Figure 10…”
Section: Batemo 2 O 9 (Btm)mentioning
confidence: 99%
See 3 more Smart Citations
“…In 2012, Yu et al confirmed that the BTM crystal has a wide transmission band (0.4-5 µm), large nonlinear coefficient (d 31 = 9.88 pm/V) and high optical damage threshold (544 MW/cm 2 ), flexible phase-matching, and high chemical, and mechanical stabilities [116]. Its strongest Raman shift is 915.2 cm −1 with line width of~4.4 cm −1 [6]. In 2013, the BTM crystal was employed as self-frequency-doubled Raman crystal to generate the yellow laser at 589 nm, as illustrated in Figure 10…”
Section: Batemo 2 O 9 (Btm)mentioning
confidence: 99%
“…For instance, in 2009, Liu et al [5] used a single KTA crystal to perform self-frequency-doubled Raman conversion from the 1064 nm fundamental beam to the 573 nm yellow beam. Another self-frequency-doubled Raman crystal, BTM, was reported by Gao et al [6] in 2013, and a maximum pulse energy of 5.6 mJ was attained for 589 nm yellow laser radiation.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In order to simplify the laser configuration, the self-Raman laser for rare-earth doped crystals, including Nd:YVO 4 , 5 Nd:GdVO 4 , 6 and Yb:KGd(WO 4 ) 2 , 7 have been applied as laser and SRS crystals simultaneously. Recently, both the molybdate and tungstate, such as CaMoO 4 , 8 SrMoO 4 , 9 BaTeMo 2 O 9 , 10,11 BaWO 4 , 12 SrWO 4 , 13 and CaWO 4 , 8 have been paid attention owing to their excellent SRS properties. Although the above molybdate and tungstate crystals exhibit excellent Raman property, they are difficult for rare-earth doping due to the mismatch of their cation valence.…”
Section: Introductionmentioning
confidence: 99%